Friction screening test method for wet multi-plate clutches - Stockinger, Ulrich; Acuner, Robert; Voelkel, Katharina; Pflaum, Hermann; Stahl, Karsten (International Journal of Powertrains, 2021)
Knowing the friction behaviour of wet multi-plate clutches is crucial when developing a new clutch system. Many parameters, which cannot be predicted or determined by simulations, influence the friction behaviour. This is why developing new transmission fluids and friction linings requires experiments. This paper describes an efficient test method to determine the friction behaviour of different types of friction linings with different lubricants. The experiments’ results characterise influences of additives on the friction behaviour for the running-in process, over various load stages, and during continuous shifting tests. The method is introduced to repeatably and reproducibly evaluate the coefficient of friction and tendency of the clutch to shudder.
CRIS-Team Scopus Importer:2025-05-19
Keywords: Additive effects; Carbon friction lining; Data evaluation; Friction screening test method; Multi-plate clutch; Paper friction lining; Sinter friction lining